Induction of plasticity in the human motor cortex by pairing an auditory stimulus with TMS - Sowman, Paul F.; Dueholm, Søren S.; Rasmussen, Jesper H.; Mrachacz-Kersting, Natalie (Frontiers in Human Neuroscience, 2014)
Acoustic stimuli can cause a transient increase in the excitability of the motor cortex. The current study leverages this phenomenon to develop a method for testing the integrity of auditorimotor integration and the capacity for auditorimotor plasticity. We demonstrate that appropriately timed transcranial magnetic stimulation (TMS) of the hand area, paired with auditorily mediated excitation of the motor cortex, induces an enhancement of motor cortex excitability that lasts beyond the time of stimulation. This result demonstrates for the first time that paired associative stimulation (PAS) -induced plasticity within the motor cortex is applicable with auditory stimuli. We propose that the method developed here might provide a useful tool for future studies that measure auditory-motor connectivity in communication disorders.